2000
DOI: 10.4049/jimmunol.165.11.6400
|View full text |Cite
|
Sign up to set email alerts
|

A Single 3′α hs1,2 Enhancer in the Rabbit IgH Locus

Abstract: Multiple cis-acting elements including the intronic enhancer and the 3′α enhancer (3′αE) regulate expression of the Ig heavy chain genes during B cell development. A 3′αE is composed of DNase I-hypersensitive sites, hs1,2, hs3a,b, and hs4, found 3′ of the murine Cα gene as well as 3′ of both human Cα genes, Cα1 and Cα2. Rabbits have 13 Cα genes, and we tested whether a 3′αE is associated with each of these genes. To identify 3′αE regions we developed a rabbit hs1,2 probe and used this to search for enhancer ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Two BACs hybridized with the two probes specific for rabbit VH1 and DH, three BACs hybridized with the Cg probe. Screening of the library with a probe specific for the recently identified rabbit heavy chain 3V enhancer region (Volgina et al, 2000) did not result in the identification of any positive BAC clone. Similarly, screening of a second library (kindly provided by Dr. Jan-Fang Cheng, Lawrence Berkeley National Laboratory) consisting of 120,804 BAC clones with an average insert size of 175 kb (corresponding to 7.0 times the rabbit genome) also did not identify BAC clones hybridizing with this 3V enhancer probe.…”
Section: Library Screeningmentioning
confidence: 86%
See 2 more Smart Citations
“…Two BACs hybridized with the two probes specific for rabbit VH1 and DH, three BACs hybridized with the Cg probe. Screening of the library with a probe specific for the recently identified rabbit heavy chain 3V enhancer region (Volgina et al, 2000) did not result in the identification of any positive BAC clone. Similarly, screening of a second library (kindly provided by Dr. Jan-Fang Cheng, Lawrence Berkeley National Laboratory) consisting of 120,804 BAC clones with an average insert size of 175 kb (corresponding to 7.0 times the rabbit genome) also did not identify BAC clones hybridizing with this 3V enhancer probe.…”
Section: Library Screeningmentioning
confidence: 86%
“…In the mouse, one enhancer region is found 3V of Ca, while the human locus contains two enhancer regions downstream of both, Ca1 and Ca2 (Birshtein et al, 1997;Mills et al, 1997). Rabbits have 14 Ca genes, but only a single hs1,2 enhancer element downstream of the 3V-most rabbit Ca13 gene was identified (GI: 1154561) (Knight et al, 1984;Spieker-Polet et al, 1993;Volgina et al, 2000). Sequencing of Fos15B revealed besides hs1,2 (6 kb downstream of Ca13) sequences with 92% and 84% sequence identity with human and mouse hs4, respectively.…”
Section: V Enhancer Elementsmentioning
confidence: 96%
See 1 more Smart Citation
“…The structure, and possibly the function, of the enhancers situated in the immunoglobulin regulative region, at the 3V end of the constant heavy chain cluster, is largely conserved from mouse to human (Mills et al, 1997), although in rabbit only one 3V enhancer is present after 13 copies of the constant heavy a gene (Volgina et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Volgina et al (32) reported that the rabbit IgH locus has a single 3Ј␣ (hs1, 2) enhancer, and while this element significantly enhanced the activity of a V H promoter, it had little effect on an I␣ promoter. We suggest that neither the strength of the I␣ promoters nor the 3Ј␣ (hs1, 2) enhancer is responsible for the differential expression of IgA isotypes in vivo.…”
Section: Discussionmentioning
confidence: 99%